A new recognition moiety diphenylborinate in the detection of pyruvate via Lewis acid/base sensing pathway and its bioimaging applications - Rajalakshmi, K.; Muthusamy, S.; Nam, Y.-S.; Li, Y.; Lee, K.-B.; Xu, Y. (Pergamon Press Ltd., 2022)
Developing new reaction based recognizing units can enhance the specificity of target analyte molecules in practical applications of real samples and biosystems. Therefore, introducing a recognizing moiety diphenylborinate was encountered for the detection of pyruvate biomolecule through Lewis acid-base reaction based sensing strategy. The construction of the Schiff-base back bone between quinoline and N-(diethylamino)salicylaldehyde-diphenylborinate (QSB) were expressed the red shift from blue emission of quinoline in to green as that of dative bond developed between Schiff base nitrogen and boron atoms. The new sensing approach was involved such a way that fluorophore QSB is a Lewis acid while pyruvate acts as Lewis base, where the elimination of Lewis pair produced a weak green fluorescence including the formation of quinoline, N-(diethylamino)salicylaldehyde (QS). The switching products were witnessed through 1H NMR titration, HR-MS and FT-IR studies. The good selectivity and interference ability were achieved in presence of 1000-fold excess of possible interferences with LOD of 16 nM. Moreover, the tracking ability of the probe was employed towards pyruvate in live HeLa cell imaging for evaluating an exogenous and endogenous signals producing ability and its mitochondria targeting property was investigated successfully. Further, the practical utility of the probe was tested with milk samples and obtained good recovery results. ？ 2021 Elsevier B.V.